Low-density lipoprotein receptor-related protein 6 ameliorates cardiac hypertrophy by regulating CTSD/HSP90α signaling during pressure overload - Pan Le; Yin Chao; Jin Ke-jia; Huang Chen-xing; Wang Xiang; Wang Ying; Rinkiko Suguro; Jia Jian-guo; Zhang Guo-ping; Zhu Yi-zhun; Dai Yu-xiang; Zou Yun-zeng; et al. (Acta Pharmacologica Sinica, 2025)
Pressure overload induces pathological cardiac remodeling, including cardiac hypertrophy and fibrosis, resulting in cardiac dysfunction or heart failure. Recently, we observed that the low-density lipoprotein receptor-related protein 6 (LRP6), has shown potential in enhancing cardiac function by mitigating cardiac fibrosis in a mouse model subjected to pressure overload. In this study, we investigated the role of LRP6 as a potential modulator of pressure overload-induced cardiac hypertrophy and elucidated the underlying molecular mechanisms. We performed transverse aortic constriction (TAC) to induce pressure overload in cardiomyocyte-specific LRP6 overexpression mice (LRP6-over mice) and in control mice (α-myosin heavy chain (α-MHC) Mer-Cre-Mer Tg mice or named MCM mice). Cardiac function and hypertrophy were assessed using echocardiography. LRP6-over mice showed improved cardiac function and reduced hypertrophy after TAC, compared with MCM mice. We also applied mechanical stretch to cultured neonatal rat cardiomyocytes to model pressure overload in vitro. Mass spectrometry analysis showed that LRP6 interacts with HSP90α and cathepsin D (CTSD) in cardiomyocytes under mechanical stress. Further analysis demonstrated that LRP6 facilitates CTSD-mediated degradation of HSP90α, consequently inhibiting β-catenin activation and reducing cardiac hypertrophy post-TAC. Treatment with recombinant HSP90α protein or the CTSD inhibitor, pepstatin A, partly abolished the protective effect of LRP6 overexpression on myocardial hypertrophy and cardiac function after TAC in mice. Collectively, our data suggest that LRP6 protects against pressure overload-induced myocardial remodeling and that the CTSD/HSP90α/β-catenin axis may be a potential therapeutic target.